Waste Recycling, An Example Of Refuse Collecting As A Means Of Livelihood In The Informal Sector Of Nsukka Urban Area, Enugu State, Nigeria. - Ogbu , S. Okonkwo; Ajadike , J. C.; Ugwu, Hillary Ndubuisi (Archives of Business Research, 2019)
This study explored how picking waste materials has aided sustenance in the livelihood of scavengers, an informal sector in Nsukka urban area of Enugu State, Nigeria. It aimed at identifying the demographic and socioeconomic characteristics of scavengers as well as the type and uses of collected waste materials. Survey research design was adopted in this study. A total of 411 scavengers (45.7%) were sampled out of the available 900 scavengers in the four administrative units of Nsukka Urban area as follows; Ihe/Owerre (165), Obukpa (82), Nru (82) and Mpkunano (82). The data were collected using the instrument of questionnaire, oral interview, and field observation. Data obtained were analyzed using percentage and rank methods, graphs (especially bar and pie graphs), and KrusKal-Wallis statistical techniques. The socioeconomic features of the respondents identified were; gender (males, 88.8% and females 11.2%); age (5-25years (19.4%), 26-45years (47.2%), and above 46 years (33.4%)); education (non-formal education (13.4%), FSLC (46.6%), GCE/SSCE (36.4%), OND (2.0%), HND (1.0%) and B Sc/B.A. (0.6%)); and Marital status (single (64.4%),and married (6.6%), widowed (17.8%) and divorced (11.2%)). The results obtained reveal that useful materials collected in the area originate in descending order from metals (54.6%), glass (23.8%), Plastics (10.4%), foods (6.2%), and papers (5.0%). These materials are found to be useful in two major areas of sales as source of income (78.2%), and for domestic purposes (21.8%). The ranges of income derived from scavenging in the area vary from below N2, 000.00 to above N20, 000.00 per month with N10, 001.00 - N20, 000.00 (39.2%) dominating other income levels. From these results, it is recommended that scavenging business should be encouraged by government and industrialist through the establishment of industrial activities that recycle and use recycled materials as input materials in the study area.